Faktor Penyebab Bayi 0-12 Bulan Terjangkit Diare, Dan Hubungan Dengan Pemberian Asi Eksklusif Di Desa Cinta Rakyat Jalan Teruno Joyo - Rahmawani Fauza (Pusdikra Publishing, 2022)
Diarrhea is an endemic disease with the potential for extraordinary events that are often accompanied by death in Indonesia (Ministry of Health of the Republic of Indonesia 2020). As in the previous year, in 2020, pneumonia and diarrhea were still the main problems causing 73.9% of deaths (pneumonia) and 14.5% of deaths (diarrhea). (Indonesia health profile 2020).This study aims to make mothers aware of the importance of exclusive breastfeeding for infant health, and to know the prevention of diarrhea so that it does not continue to get worse which can lead to death. The method used in this research is quantitative. This research was conducted quantitatively because the researcher wanted to get extensive information from a population, knowing the extent of treatment on a particular subject. Based on the table above, the factors that affect diarrhea in infants 0-1 years in Cinta Rakyat found 80%) of the respondents who had exclusively breastfed their babies, and (20%) for mothers who gave formula milk to their babies, from mothers who Breastfeeding (12.5%) of the 24 respondents who had a history of contracting diarrhea to their babies, while mothers who gave formula milk were (100%) of 6 respondents